Test Reliability Analysis in Educational Evaluation: A Quantitative Approach to Consistency and Validity - Arbeni, Wawan; Windiani, Astina; Sihotang, Demak Sariyani Br; Anggraini, Nova; Wulandari, Siska; Nugroho, Arga (Holistic Science, 2025)
Test reliability is a fundamental aspect in educational evaluation, reflecting the extent to which a test produces consistent results under various conditions. This study aims to analyze the reliability of the developed test, with a quantitative approach using statistical analysis such as Cronbach's Alpha coefficient, inter-rater reliability, and temporal stability test. Content validity is also a major concern in the preparation of the test to ensure suitability with the measurement objectives. Empirical data were collected through a trial on a group of respondents, then analyzed to measure internal consistency and stability of the results. The results showed that the developed test had high reliability, with a Cronbach's Alpha coefficient exceeding 0.70, as well as good consistency between raters. However, several aspects such as item construction and distribution of difficulty levels need to be improved. This study recommends further testing with a wider population and integration of technology in the evaluation to improve measurement accuracy. These findings emphasize the importance of developing valid and reliable evaluation instruments to improve the quality of educational assessment.